- PENDEKATAN KOMPUTASI UNTUK MENGATASI MALARIA DARI Coscinium fenestratum - Hadi, samsul samsul; Nastiti, Kunti (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2023)
Malaria is a disease with signs of fever and is caused by Plasmodium. One way to inhibit the growth of plasmodium is using Dihydroorotate dehydrogenase inhibitors. The method used in this study was docking with laptop aspireÂ ES 14 equipment and PLANTS software for docking and the Discovery Studio for visualization and the materials used were compounds contained in C. fenestratum. This research was carried out using protein code 6VTY which removed water molecules and ligands that were not linked to the active site, and continued with the docking of the compounds contained in C. fenestratum. The results of this study are the Berberine docking score -82.2408; Berberrubine -84.6866 and Thalifendine -81.1591, the result of ligand interaction with Dihydroorotate dehydrogenase, the three ligands occupy the catalytic site of the enzyme, namely HIS185, PHE227, ARG 265 and CYS 175. The conclusion in this study is Berberrubine with a docking score of -82.488 is compounds that have the potential as Dihydroorotate dehydrogenase inhibitors